(untitled) (Nexus International Journal of Science and Education, 2024)
The study assessed the relationship between School Learning Action Cells Implementation Self-Efficacy in Junior High School Students in Sta Cruz North District, Davao del Sur Schools Division. This used a non-experimental descriptive-correlational research design, utilizing an adapted survey instrument to gather responses from the randomly selected 120 teacher-respondents. The treatments used were Mean scores with descriptive interpretation, Pearson r, and Simple Linear Regression Analysis. Findings revealed that the extent of school learning action cells implementation which content and pedagogy, learner diversity and student inclusion, curriculum context, localization and indigenization, assessment and reporting, and ICT integration in instruction and assessment are sometimes manifested, the extent of self-efficacy in junior high school students of which problem-solving confidence and persistence are oftentimes manifested; while performance expectations and task-specific confidence are sometimes manifested. There is a significant relationship between school learning action cells and self-efficacy in junior high school students. All domains of School Learning Action Cells implementation significantly influenced self-efficacy in junior high school students. Future research may investigate the scalability of successful practices in different educational contexts.